Anterior Shoulder Instability and Open Procedures: History, Indications, and Clinical Outcomes - Fares, Mohamad Y.; Boufadel, Peter; Daher, Mohammad; Koa, Jonathan; Khanna, Akshay; Abboud, Joseph A. (Clinics in orthopedic surgery, 2023)
The shoulder, being the most mobile joint in the human body, is often susceptible to dislocations and subluxations more so than other joints. As such, shoulder instability constitutes a common complaint among patients worldwide, especially those who are young, participate in contact sports, and have increased innate flexibility in their joints. Management options in the setting of instability vary between conservative and surgical options that aim to mitigate symptoms and allow return of function. Surgical options can be arthroscopic and open, with a general shift among surgeons towards utilizing arthroscopic surgery in the past several decades. Nevertheless, open procedures still play a role in managing shoulder instability patients, especially those with significant bone loss, recurrent instability, coexisting shoulder pathologies, and high risk of failure with arthroscopic surgery. In these clinical settings, open procedures, like the Latarjet procedure, open Bankart repair, glenoid bone augmentation using iliac crest autograft or distal tibial allograft, and salvage options like glenohumeral arthrodesis and arthroplasty may show good clinical outcomes and low recurrence rates. Each of these open procedures possesses its own set of advantages and disadvantages and entails a specific set of indications based on published literature. It is important to cater treatment options to the individual patient in order to optimize outcomes and reduce the risk of complications. Future research on open shoulder stabilization procedures should focus on the long-term outcomes of recently utilized procedures, investigate different graft options for procedures involving bone augmentation, and conduct additional comparative analyses in order to establish concrete surgical management guidelines.